Superior Vena Cava Syndrome in the Immediate Postoperative Period After Biatrial Heart Transplantation - Francisco J. González-Ruiz; Gerardo Salazar-Ceceña; Luis A. Baeza-Herrera; Victor J. Leal-Alcántara; Angel Ramos-Enriquez; Emanuel A. Lazcano-Díaz; Nahin E. Inoa-Portes; Efrén Santos-Martínez; José A. García-Montes (Annals of Internal Medicine: Clinical Cases)
Superior vena cava syndrome represents a medical condition characterized by a constellation of signs and symptoms, the most feared complication being cerebral edema. To our knowledge, there are no reports in the literature of vena cava syndrome in patients with bicaval heart transplants with successful resolution through endovascular intervention and its outcomes. We present the case of a 59-year-old woman with Ebstein anomaly in refractory heart failure who had a biatrial heart transplant and presented with superior vena cava syndrome after surgery. The patient underwent interventional treatment, which was successful and remarkably free of complications, and was discharged from the hospital.